Gold nanoparticle-based platforms for vaccine development. (December 2020) - Mateu Ferrando, Ruth; Lay, Luigi; Polito, Laura
Graphical abstract: Abstract : Since their discovery, therapeutic or prophylactic vaccines represent a promising option to prevent or cure infections and other pathologies, such as cancer or autoimmune disorders. More recently, among a number of nanomaterials, gold nanoparticles (AuNPs) have emerged as novel tools for vaccine developments, thanks to their inherent ability to tune and upregulate immune response. Moreover, owing to their features, AuNPs can exert optimal actions both as delivery systems and as adjuvants. Notwithstanding the potential huge impact in vaccinology, some challenges remain before AuNPs in vaccine formulations can be translated into the clinic. The current review provides an updated overview of the most recent and effective application of gold nanoparticles as efficient means to develop a new generation of vaccine.